Peran dan Strategi Indonesia bersama ASEAN Dalam Upaya Meredakan Konflik Laut China Selatan [The Role and Strategy of Indonesia with ASEAN to Reduce Conflict in the South China Sea] - Aditya Haryo Wahyudi (Universitas Pelita Harapan, 2016)
The conflict in the South China Sea which took place from 1992 until July 2016 needs to be immediately resolved. The Government of Indonesia has seen many stakeholders strive to alleviate the conflict in a peaceful manner. ASEAN as a regional forum for countries in the region has recognized that Indonesia would need group support to confront China's increasingly unstoppable influence.It can be seen that in the South China Sea conflict, Indonesia has played a part in the formation of Declaration of Conduct between ASEAN and China and has also established a trust building workshop with the participants. It is extremely important to note that efforts made by the Government of Indonesia in carrying out its role of leadership is absolutely necessary to building mutual trust among the ASEAN countries. Moreover, together with ASEAN, Indonesia will need to be able to continue working together in the face of pressure and influence coming from China.